A rare heterochromatic variant of chromosome 4. Issue 6 (December 1984) - Docherty, Z; Bowser-Riley, S M
Abstract : A variant chromosome 4 with a large G positive heterochromatic block is described and discussed in relation to chromosome 4 heteromorphisms observed with other banding techniques. The extra heterochromatin is C positive and fluoresces brilliantly with Q banding, but differs from Yqh with some methods of staining.